Hotel Services Quality for Tourists in Transit - CAMPOVERDE AGUIRRE, Ronald; CARVACHE-FRANCO, Mauricio; CARVACHE-FRANCO, Wilmer (Journal of Environmental Management and Tourism; Vol 12 No 4 (2021): JEMT Volume XII Issue 4(52) Summer 2021, 2021)
This article aims to empirically validate a perception model of hotel service quality for short-stay tourists in transit by applying the SERVPERF model. Thus, 364 foreign tourists in transit in Guayaquil, Ecuador, whose final destination was the Galapagos Islands, were interviewed. The Confirmatory Factor Analysis (CFA) multivariate technique was adopted to evaluate the scales' validity and reliability. The results confirm the SERVPERF model’s psychometric properties for the hotel services quality evaluation. The findings will contribute to hotel managers decision making.